Pendekatan perbandingan cerun untuk pengaturcaraan linear - Majid, Mohd. Yunus (Penerbit UTM Press, 1990)
Linear programming is not a new field in mathematical problem solving. Until today, various methods and approaches have been invented for solving linear programming problems. One of the methods normally used is the revised simplex . For complex problems, solved manually using revised simplex , it requires time and understanding of matrices in addition to its complexity in calculation. At the same time, due to number of iterations that has to be done, the probability of error is high. Consequently, a new method for solving linear programming problems called the Comparison of slopes was designed. Generally, this method makes comparison of the slopes of the constraints and the objective function. As a start, the scope of this study only encompasses problems of two variables.